Retrospective study on mucocutaneous manifestations due to COVID-19 in paediatric age group in a tertiary care centre in Southern India - Malathy, Priyavathani Annie; S., Thamizhselvi; H. R., Poornima (International Journal of Research in Dermatology, 2022)
Background: COVID-19 virus is known to cause wide variety of mucocutaneous manifestations . The inflammatory response of body plays a crucial role in SARS-CoV-2 induced lung injury.These cytokines arriving at the skin and reaching various cells of cutaneous immune system can cause dermatological lesions described during COVID-19 infection.The primary aim of this study is to characterize the diversity of cutaneous manifestations due to COVID-19 in pediatric age group. Methods: The study was an observational study done on paeadiatric COVID cases aged less than 12 years who were admitted in COVID isolation ward of Institute of Child Health, Rajiv Gandhi Government General Hospital. This study was conducted for 3 months from August 2020 to October 2020. Results: A total of 191 swab-confirmed cases of COVID-19 aged less than 12 years were recruited in the study. Out of 191 cases, 19 had dermatological manifestations (10%).The most common type of dermatological manifestation noted in our study was maculopapular rash (N=8) , followed by purpura (N=4),urticarial (N=3), angular cheilitis (N=2), palmar erythema (N=1), purpura with palmar erythema occurring together (N=1). Time latency between onset of first COVID symptom and occurrence of cutaneous lesion was 1 to 7 days. Conclusions: A total of 191 swab-confirmed cases of COVID-19 aged less than 12 years were recruited in the study. Out of 191 cases, 19 had dermatological manifestations (10%). The most common type of dermatological manifestation noted in our study was maculopapular rash (N=8) , followed by purpura (N=4),urticarial (N=3), angular cheilitis (N=2), palmar erythema (N=1), purpura with palmar erythema occurring together (N=1). Time latency between onset of first COVID symptom and occurrence of cutaneous lesion was 1 to 7 days.